2013
DOI: 10.1088/1367-2630/15/12/123001
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of the new multiferroic material (NH4)2[FeCl5(H2O)]

Abstract: NH 4 ) 2 [FeCl 5 (H 2 O)], a member of the family of antiferromagnetic A 2 [FeX 5 (H 2 O)] compounds (X = halide ion and A = alkali metal or ammonium ion) is classified as a new multiferroic material. We report the onset of ferroelectricity below 6.9 K within an antiferromagnetically ordered state (T N 7.25 K). The corresponding electric polarization can drastically be influenced by applying magnetic fields. Based on measurements of pyroelectric currents, dielectric constants and magnetization we characterize … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(136 citation statements)
references
References 42 publications
17
119
0
Order By: Relevance
“…The series of Q-scans performed with the crystal oriented with the c-axis parallel to B shows qualitatively the same results -not surprisingly, given the close similarity of the B-T phase diagrams for both orientations of the magnetic field [24] . The resolution is however markedly poorer with B//c, as the experimental geometry ('normal beam') implies measurements with a departure from the horizontal scattering plane ( Fig.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The series of Q-scans performed with the crystal oriented with the c-axis parallel to B shows qualitatively the same results -not surprisingly, given the close similarity of the B-T phase diagrams for both orientations of the magnetic field [24] . The resolution is however markedly poorer with B//c, as the experimental geometry ('normal beam') implies measurements with a departure from the horizontal scattering plane ( Fig.…”
supporting
confidence: 64%
“…Moreover, in order to include the effect of the magnetic field, a weak ferromagnetic component along the a-axis (direction of application of the external magnetic field) has been included in the model. The value of the field-induced ferromagnetic moment was derived from the magnetization curves as function of the external field [24] , with an estimated value of 0.4  B along the a-axis. shows two remarkable differences with respect to the previously obtained at zero field [26] .…”
mentioning
confidence: 99%
“…This offers a unique opportunity to test theoretical models that will shed light on the underlying multiferroic mechanism. In this paper, we report a neutron diffraction study of (NH 4 ) 2 FeCl 5 ·H 2 O, a molecular compound that was recently discovered to exhibit magnetically induced multiferroicity [19]. Using both polarized and unpolarized neutrons, we show that the onset of the electric polarization is accompanied by a lattice modulation indicating spin-lattice coupling plays a critical role in the ferroelectric mechanism…”
mentioning
confidence: 91%
“…Combined with the large magnetostriction and negative thermal expansion [19] Note: While working on the revision of this paper, we become aware of a recent work by Rodríguez-Velamazán et al which reports that no higher-order harmonics and coexistence of the IC and C phases were observed in their experiment on the same material [34].…”
mentioning
confidence: 99%
“…Compared to conventional ferroelectrics, the spontaneous electric polarizations are often rather small, but can be strongly modified and controlled by external magnetic fields. As a result of the intense research activities, a series of new spin-driven multiferroic materials has been found in the last few years; see for example [6][7][8][9][10][11][12][13][14][15][16][17]. In particular the pyroxenes (general formula AMX 2 O 6 with A = mono-or divalent metal, M = di-or trivalent metal and X = tri-or tetravalent cation) form a huge family of potentially multiferroic and magnetoelectric materials [18].…”
Section: Introductionmentioning
confidence: 99%